ANALISIS STRUKTUR BENTUK MUSIK LAGU “BLESSINGS’ LAURA MIXON STORY ELVINGTON - Novita Febriani; Dwi sutrianto; Epifani Omega (Universitas Kristen Immanuel, 2024)
This study aims to analyze the musical structure and lyrical meaning of Laura Story's song